2006
DOI: 10.1152/jn.00192.2006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Visual Motion on Tactile Motion Perception

Abstract: Subjects were presented with pairs of tactile drifting sinusoids and made speed discrimination judgments. On some trials, a visual drifting sinusoid, which subjects were instructed to ignore, was presented simultaneously with one of the two tactile stimuli. When the visual and tactile gratings drifted in the same direction (i.e., from left to right), the visual distractors were found to increase the perceived speed of the tactile gratings. The effect of the visual distractors was proportional to their temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 28 publications
3
43
1
Order By: Relevance
“…Consistent with our suggestion of an implicit reaction induced by the automatic activation of an S-R association, previous studies have confirmed that viewing objects with action meanings can prime manual responses related to those objects (Tucker & Ellis, 2004); such priming effects have been observed in premotor and motor cortex, parietal visuomotor cortex, and the supplementary motor area (Bensmaïa, Killebrew, & Craig, 2006;Grezes & Decety, 2002;Kiefer, Sim, Helbig, & Graf, 2011;Sim, Helbig, Graf, & Kiefer, 2014). The intrinsic perception-action links revealed by these studies constitute a core notion of embodied cognition, which posits that perception and cognition can be appropriately understood only in terms of sensorimotor interaction (Engel et al, 2013;Varela, Thompson, & Rosch, 1991).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our suggestion of an implicit reaction induced by the automatic activation of an S-R association, previous studies have confirmed that viewing objects with action meanings can prime manual responses related to those objects (Tucker & Ellis, 2004); such priming effects have been observed in premotor and motor cortex, parietal visuomotor cortex, and the supplementary motor area (Bensmaïa, Killebrew, & Craig, 2006;Grezes & Decety, 2002;Kiefer, Sim, Helbig, & Graf, 2011;Sim, Helbig, Graf, & Kiefer, 2014). The intrinsic perception-action links revealed by these studies constitute a core notion of embodied cognition, which posits that perception and cognition can be appropriately understood only in terms of sensorimotor interaction (Engel et al, 2013;Varela, Thompson, & Rosch, 1991).…”
Section: Discussionsupporting
confidence: 91%
“…For instance, tactile motion can bias direction judgments of faint or ambiguous visual motion stimuli (Blake et al, 2004;Pei et al, 2013). Moreover, visual motion stimuli have been shown to influence speed perception of tactile motion, especially when both stimuli move in the same direction, i.e., when motion across modalities is congruent (Bensmaia et al, 2006). Thus, visuotactile motion congruence enhances the interplay between visual and tactile stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The initially excitatory effect of pin indentations observed at a 6-ms delay (top left figure) has changed to an inhibitory effect due to relative refractoriness in this SA fiber. Sequence of snapshots depicting a spatio-temporal sinusoid (with a spatial period of 5 mm) drifting across the array (similar to those presented in Bensmaia et al, 2006c). Because the density of the pins exceeds the innervation density in the glabrous skin of humans, the stimulus is perceived as a smooth, undulating surface.…”
Section: Applicationsmentioning
confidence: 99%
“…For instance, a spatio-temporal sinusoid (such as those presented in Bensmaia et al, 2006c) can be generated using the appropriate mathematical function (Fig. 10).…”
Section: Applicationsmentioning
confidence: 99%